2019
DOI: 10.1002/lsm.23127
|View full text |Cite
|
Sign up to set email alerts
|

Optical Access to Arteriovenous Cerebral Microcirculation Through a Transparent Cranial Implant

Abstract: Background and Objective Microcirculation plays a critical role in physiologic processes and several disease states. Laser speckle imaging (LSI) is a full‐field, real‐time imaging technique capable of mapping microvessel networks and providing relative flow velocity within the vessels. In this study, we demonstrate that LSI combine with multispectral reflectance imaging (MSRI), which allows for distinction between veins and arteries in the vascular flow maps produced by LSI. We apply this combined technique to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Therefore, brain imaging has been predominantly demonstrated in rodent open-skull and thinned skull models. Likewise, in our own prior studies we have found that optical imaging through the intact skull of mice diminishes detection of the intrinsic optical signals [24][25][26][27] . Moreover, the optical properties of the inhomogeneous cranial bone overlap with those of brain tissue and jointly these factors decrease the accuracy and reliability of the data.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, brain imaging has been predominantly demonstrated in rodent open-skull and thinned skull models. Likewise, in our own prior studies we have found that optical imaging through the intact skull of mice diminishes detection of the intrinsic optical signals [24][25][26][27] . Moreover, the optical properties of the inhomogeneous cranial bone overlap with those of brain tissue and jointly these factors decrease the accuracy and reliability of the data.…”
Section: Introductionmentioning
confidence: 69%
“…Conventional cranial prosthesis including titanium, alumina, and acrylic 37 , have not provided the requisite combination of transparency and toughness required for clinically-viable transparent cranial implants. To address this challenge, our group has previously introduced a transparent nanocrystalline yttria-stabilized-zirconia cranial implant material, which possesses the mechanical strength and biocompatibility which are prerequisites for a clinically-viable permanent cranial implant for patients [24][25][26][27][38][39][40][41][42][43][44][45][46] . This implant has been referred to in the literature as the "Window to the Brain" (WttB) implant.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of such phantoms will pave the way for designing and characterizing novel infrared multispectral imaging systems for cerebral hemodynamics monitoring, such as directly monitoring the intracranial site of the patient [24,25]. As far as we know, this is the first work that reports the optical characterization of a brain tissue-like phantom within the infrared range (i.e., 800-820 nm) using agarose.…”
Section: Introductionmentioning
confidence: 96%
“…Ceramics of 8 mol yttria stabilized zirconia (8YSZ) have been proposed as an acoustic window-to-the-brain (AWttB) that transmits up to 80.8% of the ultrasonic energy at certain thicknesses; this effect depends on a resonant behavior related to the ultrasound wavelength in the material [13]. The use of this specific material responded to a double intended use in which the window can be translucent for both optical and acoustical [13] energies for new opto-acoustic applications, besides the already presented in Optics [20]. Although 8YSZ transmits light at 1 mm thickness [21], it needs to be clarified if its transmission level is enough at the average human cranium thickness, which ranges from about 3 mm to 15 mm [22].…”
Section: Introductionmentioning
confidence: 99%